Development of mobile location based notification for crime cases tracking as an alternative alert for public safety / Noraini Ismail - Ismail, Noraini (2014)
Today, the public finds the info about crime cases activity in their neck of the woods from the read in the social media services, or requested the information from the police department. This study is to develop a system for Crime cases that capable for public or police officer to get an alert notification regarding of criminal hotspot. User also can search manually the crime cases in their neighborhood based on the current location (longitude and latitude). This study has been carried on to introduce Location Based Services (LBS). In order to develop the application with Android platform and Java, the researcher is using Eclipse IDE to support the development and use a SQLite database to store the data. The result showed that average speed of access to receive alert notification are 7.77 sec, 7.34 sec, 6.95 sec and 6.41 sec for GSM, 3g, GPS and WLAN accordingly.